RESEARCH OF SAFE METHODS OF PRODUCTION OF CANNED VEGETABLES USING GRAIN CROPS - Лаура Каликуловна Сенгирбекова (Алматы технологиялық университетінің хабаршысы, 2022)
This article presents microbiological study of canned vegetable snacks replaced with various cereals.Currently both abroad and in our country, regulatory documents and recommendations on ensuring quality and safety of foodsare actively developed. The quality reduction and food spoilage may be related to biochemical (fermentative) processes inherent to products themselves. As another important factor, influencing on this can be microbiological contaminants.Miroorganisms constantly contaminates on surface of technological equipments, vegetables raw material and as a result they end up in canned food. Canned vegetable snacks are ready meals, made from vegetables processedin various ways, that can be usedcold and heated.The main purpose is studying microbiological indicators of canned vegetable snacks. According to the results of the study, some types of microorganisms were found in the samples.